Kontribusi Mazhab Bashrah dan Kufah dalam Perkembangan Teori Ibdal: Studi Komparatif Pendekatan Historis - Rosalia Indah (Pusat riset dan Inovasi Nasional, 2025)
This article examines the contributions of two major schools of Arabic grammar, the Basran and Kufan schools, to the development of the theory of ibdal (phonetic substitution) in the Arabic language. Using a historical and comparative approach, it traces the origins of the concept of ibdal in classical Arabic linguistic tradition and explores how leading grammarians from each school shaped distinct theoretical frameworks. The Basran school typically approached ibdal with a logical and systematic perspective, emphasizing phonetic patterns and structured rules of sound transformation. In contrast, the Kufan school adopted a more flexible stance, prioritizing the realities of spoken Arabic usage even if not always supported by formal phonetic justification. This study highlights not only the methodological differences between the two schools but also their long-lasting impact on the grammatical structure of Arabic. The discussion underlines the intellectual dynamics within Arabic grammar scholarship and encourages further exploration into how classical ibdal theories can inform modern linguistic analysis in Arabic studies.